1970
DOI: 10.1128/jvi.6.2.199-207.1970
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Specific Deoxyribonucleic Acid in Simian Virus 40-Exposed Hamster Cells: Correlation with S and T Antigens

Abstract: Several homologous hamster embryonic cell lines, transformed in association with simian virus (SV) 40 infection, were examined for the presence of deoxyribonucleic acid (DNA) complementary to SV40 ribonucleic acid (RNA) made in vitro. The methods employed permitted the detection of 10 −5 μg of viral DNA in 100 μg of cellular DNA, corresponding to one-fifth of an SV40 DNA molecule per cell. Those lines which contained both the SV40 surface (S) and tumor (T) antigens also contained DNA co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

1971
1971
1977
1977

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 25 publications
1
12
1
Order By: Relevance
“…The values obtained for the different polyoma-transformed and tumor cells are listed in Table 3. They are comparable to results obtained by different methods for other virustransformed cell lines (9,18,26,38). e Mouse DNA (50 ug) plus polyoma DNA (2 x 10-4 pg).…”
Section: Resultssupporting
confidence: 82%
“…The values obtained for the different polyoma-transformed and tumor cells are listed in Table 3. They are comparable to results obtained by different methods for other virustransformed cell lines (9,18,26,38). e Mouse DNA (50 ug) plus polyoma DNA (2 x 10-4 pg).…”
Section: Resultssupporting
confidence: 82%
“…These antigens were not detected in SV40-exposed hamster cells containing S, but lacking T antigen (Sq-T--) Wright, 1971). The fact that SV40-transformed mouse cells failed to show S antigen in this and a previous study (Levine et al, 1970) would indicate that anti-S antiserum might not contain the isotopic binding antibody. A more direct confirmation of this supposition is now being undertaken.…”
Section: Discussioncontrasting
confidence: 51%
“…An enumeration of all cell lines used in this study is presented in Table I. H50 and P41 were previously shown to contain SV40 S as well as T antigen (S+T+) Levine et al, 1970). All lines were propagated in monolayer with Eagle's minimal essential medium (Hanks' salts) and 2 or 10% fetal bovine serum.…”
Section: Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…DISCUSSION Previous studies using RNA-DNA hybridization and heteroduplex mapping have demonstrated that Ad2+ND, contains 43% of the wild-type SV40 genome covalently linked to Ad2 DNA (11,15). This SV40 genetic information, which includes all of the early SV40 nucleotide sequences (22), is inserted as a single segment of SV40 DNA at a point approximately 14% in from one end of the Ad2 genome (15). The fact that a significant proportion of the SV40-specific RNA synthesized during Ad2+ND, infection could be hybridized to Ad2 DNA, eluted, and rehybridized to SV40 DNA (Tables 1 and 2) indicates that at least some of the SV40 RNA sequences induced by this hybrid virus are contained in polycistronic RNA molecules which also contain Ad2 nucleotide sequences.…”
Section: Interferon Sensitivity Of Sv40 and Ad2mentioning
confidence: 93%